Cambios de la población navarra a finales del siglo XX y principios del XXI - Calvo Miranda, Juan José (Huarte de San Juan. Geografía e Historia, 2007)
This article presents the changes that have taken place in the population of Navarre between 1991 and 2005, both at the regional and municipal levels. This period has seen a change from the stagnation of the population to the fastest-known demographic increase in the region’s history, as has happened throughout Spain. The main driver in this process has been immigration by people from other countries, which accounts for 90% of real regional growth at the end of the period in question. New inhabitants have reactivated the birth rate – putting an end to the constant decline that began at the end of the 1970s – and, consequently, increased natural population growth. Over the period, on the borderline between the 20th and 21st centuries, very low population mobility has given way to a higher rate, with a high level of immigration. This is the result, above, all, of the arrival of foreigners. Their origin is increasingly varied, although the majority come from Latin America. Furthermore, their arrival has slowed down the rate of ageing of the population of the region. All these transformations are reflected differently in different places, and this has to do with the diverse nature of Navarre and other factors, among which the following stand outs: better road communications, which accelerates the suburbanisation of the larger and more dynamic population centres, particularly the Metropolitan Area of the city of Pamplona.
Keywords: Real growth; natural movements; immigration; ageing; suburbanisation; Navarre